Development of the Fruit Peels of Rambutan (Nephelium lappaceum L.) into Herbal Tea - Julinar Julinar; Dea Ananda; Huzaifah Huzaifah; Muharni Muharni; Eva Musifa (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
Rambutan (Nephelium lappaceum) peel contains various bioactive compounds, including phenolics, flavonoids, and ellagic acid, which function as antioxidants. Antioxidants are compounds needed to inhibit radical reactions and oxidation processes that trigger various diseases. This study aims to determine the potential of rambutan peel to become a herbal tea. The study began with the determination of total phenolic and flavonoid levels in aqueous extracts of rambutan peel, followed by antioxidant activity assessment using the DPPH and FRAP methods. As a comparison, tea from tea leaves (Camellia sinensis) and herbal teas from kelor (Moringa oleifera) leaves and senduduk (Melastoma malabathricum L) leaves were used. The results showed that the aqueous extract of rambutan peel had a total phenolic content of 344.07 mg GAE/g and a flavonoid content of 7.96 mg QE/g, higher than those of tea leaves, kelor leaves, and senduduk leaves. Antioxidant activity test using the DPPH method showed that rambutan peel aqueous extract is an active antioxidant with an IC₅₀ of 0.797 µg/mL, with antioxidant activity 5.45 times stronger than tea leaves, 10.33 times stronger than moringa leaves, and 4.32 times stronger than senduduk leaves. Antioxidant test using the FRAP method also showed that the antioxidant capacity of rambutan peel water extract is 29.66 mgTE/g, higher than those of tea leaves, kelor leaves, and senduduk leaves, with values of 19.84 mgTE/g, 6.12 mgTE/g, and 14.52 mgTE/g, respectively. These data indicate that rambutan peel has strong antioxidant activity and has the potential to be developed as a herbal tea.Keywords: Nephelium lappaceum peel, antioxidants, herbal tea, DPPH, FRAP